IMPLEMENTASI ADMINISTRASI KEPENDUDUKAN DI KABUPATEN MERAUKE (Perspektif Pelayanan Kartu Tanda Penduduk, Akta Kematian dan Akta Kelahiran) - Syahruddin Syahruddin (Universitas Musamus,Merauke,Papua, 2016)
This study aims to determine and describe (1) The policy implementation of public service based on Regional Regulation No. 4 of 2008 about Population Administration (Identity Card, Birth Certificate and Death Certificate). (2) The factors that affect the policy implementation among others, communication, resources, disposition, Organizational Structure in the implementation of the policy.This study used a qualitative approach to data collection techniques include interviews, documents and field observations using an interactive model of Miles and Huberman. The results showed that (1) the implementation of policy work unit area of Population and Civil Registration Merauke district in implementing the service population and civil registration services based Regional Regulation No. 4 of 2008 on Population Administration has not run optimally. (2) to implement policies by implementing policies Population Administration Office of Population and Civil Registration Merauke district in accordance with local regulations are still having problems and lack of coordination, especially in terms of communication, resources, disposition, and Organizational Structure.